Deformable high loading liquid metal nanoparticles composites for thermal energy management - Bark, Hyunwoo (2021)
The emergence of soft electronics has led to the need of thermal management with deformable material. In this perspective, eutectic gallium-indium (EGaIn) is attractive as a soft and thermal conductive material. Recent efforts have focused on incorporating EGaIn microparticles (~101 μm) into elastomer forming a thermal conductive composite. However, the shape deformation and coalescence of EGaIn particles under mechanical stress often lead to parasitic electrical conduction of the composite, posing limitation to its utilization in thermal management for the soft electronics. Increasing the loading of EGaIn nanoparticles (to over 20 vol%) often leads to brittleness of the composite. Herein, we introduce a strategy to obtain thermally conductive and soft elastomer with high volume ratio of EGaIn nanoparticles (up to 44 vol%). Surface modification of EGaIn nanoparticles with carboxylic acid terminated polydimethylsiloxane (COOH-PDMS-COOH) coupled with the in-situ formation of PDMS matrix by crosslinking with the surface-modified EGaIn nanoparticles leads to dense EGaIn nanoparticles in PDMS matrix with effective thermal transport. Notably, despite the high volume ratio of EGaIn nanoparticles (44 vol%) in the elastomer, the composite maintains a low elastic modulus (6.91 kPa) and remains electrically insulating even under mechanical stress. In addition, a distinctive anisotropic thermal conductivity of the elastomer was established upon stretching. This elastomer can be utilized as a thermal interface layer for thermoelectric device. The resulting thermoelectric performance features its promising applications in wearable thermo-haptic or thermo-sensing devices.